Analisis Efisiensi Jumlah Blade Pada Prototype Turbin Angin Venturi - Silalahi, Yosef John Kenedi; Kurniawan, Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The utilization of wind energy as electricity energy source is very limited in Indonesia. It is happened because velocity and wind direction that change. So it needs wind turbine that can be accommodate it, in particular during low wind velocity. Wind turbine that made and researched is prototype of ventury wind turbine. It is very suitable to be used for low wind velocity with high rotation velocity. In addition, it also minimum of buzzing thas’s producted by wind turbine. This study has discussed about influence of twist angle variation of blade 300 and 450, blade quantity (3 blades, 4 blades, 5 blades and 6 blades) with wind velocity (2 m/s, 3 m/s, 4 m/s, 5 m/s) to shaft rotation of wind turbine prototype and tip speed ratio (TSR). The results showed that, in 3 m/s – 4 m/s wind velocity highest rotation of wind turbine shaft is compared with another variation has done, it found in wind turbine with 3 blades and 300 twist angle, they are 190 rpm and 311 rpm. In 5 m/s wind velocity, shaft rotation velocity of prototype of wind turbine 3 blades and 450 twist angle is the highest, 385 rpm. Meanwhile, in 2 m/s wind velocity, ventury wind turbine prototype with 6 blades and 450 twist angle has rotation velocity on highest shaft, it is 52 rpm. Keywords: Ventury wind turbine, twist angle, rotation shaft, TSR